Operational Fund Management System Early Childhood Education in Dinar Playgroups in Mallawa Sub-District Mallusetasi District Barru Regency - Nurlia, Nurlia (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study aims to determine the Bop Paud Fund Management System in the Mallawa Dinar Play Group and the Target of the Bop Paud Fund Management System in the Mallawa Dinar Play Group .The object of this research is the Dinar Mallawa Play Group (kb). Data collection uses primary data in the form of interviews and secondary data in the form of collecting documentation. There are 3 (three) data analysis techniques used, namely data reduction, data display, and drawing / verivication countroling.The results showed that a fund management system was needed by a company or educational institution. It can be seen from the discussion that the fund management system has been carried out or applied in several educational institutions, especially in the system of cash in and cash out. The fund management system that has been running well in the education institution, will greatly assist the educational institution to prevent fraud in the difference between cash in and cash out and no misuse actions that can harm educational institutions. Keywords: Early Childhood Education, Organizers' Operational Fund Management System.